Two-proton correlations from 14.6A GeV/c Si+Pb and 11.5A GeV/c Au+Au central collisions - Barrette, Jean; Stachel, Johanna; Wessels, Johannes P. (Arxiv, 1999)
Two-proton correlation functions have been measured in Si+Pb collisions at 14.6A GeV/c and Au+Au collisions at 11.5A GeV/c by the E814/E877 collaboration. Data are compared with predictions of the transport model RQMD and the source size is inferred from this comparison. Our analysis shows that, for both reactions, the characteristic size of the system at freeze-out exceeds the size of the projectile, suggesting that the fireball created in the collision has expanded. For Au+Au reactions, the observed centrality dependence of the two-proton correlation function implies that more central collisions lead to a larger source sizes.
Gesehen am 26.02.2020